Question

Find laplace transform of each following a) displaystyle{t}^{n} b) displaystyle cos{omega}{t} c) displaystyle sin{{h}}{left({c}{t}right)} d) displaystyle cos{{h}}{left({c}{t}right)}

Laplace transform
ANSWERED
asked 2020-10-28
Find laplace transform of each following
a) \(\displaystyle{t}^{n}\)
b) \(\displaystyle \cos{\omega}{t}\)
c) \(\displaystyle \sin{{h}}{\left({c}{t}\right)}\)
d) \(\displaystyle \cos{{h}}{\left({c}{t}\right)}\)

Answers (1)

2020-10-29
ANSWER FOR (A)We have to find Laplace transform of \(\displaystyle{t}^{n}\), that is, \(\displaystyle{L}{\left\lbrace{t}^{n}\right\rbrace}\).
Now from the Laplace Transform table we know that
\(\displaystyle{L}{\left\lbrace{t}^{n}\right\rbrace}=\frac{{{n}!}}{{{s}^{{{n}+{1}}}}}\)
This shows that
\(\displaystyle{L}{\left\lbrace{t}^{n}\right\rbrace}=\frac{{{n}!}}{{{s}^{{{n}+{1}}}}}\)
ANSWER FOR (B) We have to find Laplace transform of \(\displaystyle \cos{{\left(\omega{t}\right)}}\), that is, L \(\displaystyle{\left\lbrace \cos{{\left(\omega{t}\right)}}\right\rbrace}\)
Now from the Laplace Transform table we know that
\(\displaystyle{L}{\left\lbrace \cos{{\left({a}{t}\right)}}\right\rbrace}=\frac{s}{{{s}^{2}+{a}^{2}}}\)
Whis shows that
\(\displaystyle{L}{\left\lbrace \cos{{\left(\omega{t}\right)}}\right\rbrace}=\frac{s}{{{s}^{2}+\omega^{2}}}\)
ANSWER FOR (C) We have to find Laplace transform of \(\displaystyle \sin{{h}}{\left({c}{t}\right)}\), that is, L \(\displaystyle{\left\lbrace \sin{{h}}{\left({c}{t}\right)}\right\rbrace}\)
Now from the Laplace Transform table we know that
\(\displaystyle{L}{\left\lbrace \sin{{h}}{\left({a}{t}\right)}\right\rbrace}=\frac{a}{{{s}^{2}-{a}^{2}}}\)
Whis shows that
\(\displaystyle{L}{\left\lbrace \sinh{{\left({c}{t}\right)}}\right\rbrace}=\frac{c}{{{s}^{2}-{c}^{2}}}\)
ANSWER FOR (D) We have to find Laplace transform of \(\displaystyle \cos{{h}}{\left({c}{t}\right)}\), that is, L \(\displaystyle{\left\lbrace \cos{{h}}{\left({c}{t}\right)}\right\rbrace}\)
Now from the Laplace Transform table we know that \(\displaystyle{L}{\left\lbrace \cos{{h}}{\left({a}{t}\right)}\right\rbrace}=\frac{s}{{{s}^{2}-{a}^{2}}}\)
Whis shows that
\(\displaystyle{L}{\left\lbrace \cos{{h}}{\left({c}{t}\right)}\right\rbrace}=\frac{s}{{{s}^{2}-{c}^{2}}}\)
0
 
Best answer

expert advice

Need a better answer?

Relevant Questions

asked 2021-06-06
Use the table of Laplace transform and properties to obtain the Laplace transform of the following functions. Specify which transform pair or property is used and write in the simplest form.
a) \(x(t)=\cos(3t)\)
b)\(y(t)=t \cos(3t)\)
c) \(z(t)=e^{-2t}\left[t \cos (3t)\right]\)
d) \(x(t)=3 \cos(2t)+5 \sin(8t)\)
e) \(y(t)=t^3+3t^2\)
f) \(z(t)=t^4e^{-2t}\)
asked 2021-05-16
Find the Laplace transform of the function \(L\left\{f^{(9)}(t)\right\}\)
asked 2020-10-25
Please provide steps
The inverse Laplace transform for
\(\displaystyle{F}{\left({s}\right)}=\frac{8}{{{s}+{9}}}-\frac{6}{{{s}^{2}-\sqrt{{3}}}}\) is
a) \(\displaystyle{8}{e}^{{-{9}{t}}}-{6} \sin{{h}}{{\left({3}{t}\right)}}\)
b) \(\displaystyle{8}{e}^{{-{9}{t}}}-{6} \cos{{h}}{\left({3}{t}\right)}\)
c) \(\displaystyle{8}{e}^{{{9}{t}}}-{6} \sin{{h}}{\left({3}{t}\right)}\)
d) \(\displaystyle{8}{e}^{{{9}{t}}}-{6} \cos{{h}}{\left({3}{t}\right)}\)
asked 2021-05-12
One property of Laplace transform can be expressed in terms of the inverse Laplace transform as \(L^{-1}\left\{\frac{d^nF}{ds^n}\right\}(t)=(-t)^n f(t)\) where \(f=L^{-1}\left\{F\right\}\). Use this equation to compute \(L^{-1}\left\{F\right\}\)
\(F(s)=\arctan \frac{23}{s}\)
asked 2021-02-21
Find the Laplace transforms of the following time functions.
Solve problem 1(a) and 1 (b) using the Laplace transform definition i.e. integration. For problem 1(c) and 1(d) you can use the Laplace Transform Tables.
a)\(f(t)=1+2t\) b)\(f(t) =\sin \omega t \text{Hint: Use Euler’s relationship, } \sin\omega t = \frac{e^(j\omega t)-e^(-j\omega t)}{2j}\)
c)\(f(t)=\sin(2t)+2\cos(2t)+e^{-t}\sin(2t)\)
asked 2021-02-10
Find the equation by applying the Laplace transform.
\(\displaystyle{y}^{{{\left({4}\right)}}}-{y}= \sin{{h}}{t}\)
\(y(0)=y'(0)=y"(0)=0\)
\(y'''(0)=1\)
asked 2021-01-30

Use Laplace transform to find the solution of the IVP
\(2y'+y=0 , y(0)=-3\)
a) \(f{{\left({t}\right)}}={3}{e}^{{-{2}{t}}}\)
b)\(f{{\left({t}\right)}}={3}{e}^{{\frac{t}{{2}}}}\)
c)\(f{{\left({t}\right)}}={6}{e}^{{{2}{t}}}\)
d) \(f{{\left({t}\right)}}={3}{e}^{{-\frac{t}{{2}}}}\)

asked 2021-02-19

Use Laplace transform to solve the following initial-value problem
\(y"+2y'+y=0\)
\(y(0)=1, y'(0)=1\)
a) \(\displaystyle{e}^{{-{t}}}+{t}{e}^{{-{t}}}\)
b) \(\displaystyle{e}^{t}+{2}{t}{e}^{t}\)
c) \(\displaystyle{e}^{{-{t}}}+{2}{t}{e}^{t}\)
d) \(\displaystyle{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
e) \(\displaystyle{2}{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
f) Non of the above

asked 2020-12-30
The Laplace inverse of \(L^{-1}\left[\frac{s}{s^2+5^2}\right]\) is
\(a) \cos(5t)\)
\(b) \sin h(5t)\)
\(c) \sin(5t)\)
\(d) \cos h(5t)\)
asked 2021-02-25
Use properties of the Laplace transform to answer the following
(a) If \(f(t)=(t+5)^2+t^2e^{5t}\), find the Laplace transform,\(L[f(t)] = F(s)\).
(b) If \(f(t) = 2e^{-t}\cos(3t+\frac{\pi}{4})\), find the Laplace transform, \(L[f(t)] = F(s)\). HINT:
\(\cos(\alpha + \beta) = \cos(\alpha)\cos(\beta) - \sin(\alpha) \sin(\beta)\)
(c) If \(F(s) = \frac{7s^2-37s+64}{s(s^2-8s+16)}\) find the inverse Laplace transform, \(L^{-1}|F(s)| = f(t)\)
(d) If \(F(s) = e^{-7s}(\frac{1}{s}+\frac{s}{s^2+1})\) , find the inverse Laplace transform, \(L^{-1}[F(s)] = f(t)\)
...